PENGUATAN STRATEGI PENGGERAKAN PARTISIPASI MAYARAKAT DALAM MENINGKATKAN PESERTA KB MODERN DI PROVINSI LAMPUNG - Andini, Wira Setio; Karyus, Aila; Djamaluddin, Abikusno (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
The family planning program is an effort to regulate the birth of children, the ideal distance and age to give birth, to regulate pregnancy through promotion, protection and assistance in accordance with reproductive rights to create a quality family. The COVID 19 pandemic situation has resulted in a decrease in the number of family planning participants. The purpose of this observation is to observe the phenomenon of sluggish public participation in the family planning program and determine strategies so that family planning services can reach all prospective family planning participants. This type of research is qualitative, with data collection methods using in-depth interviews and focus group discussions with family planning managers at the provincial and district levels. Observations were carried out in May until June 2022. The results obtained were that community participation in the modern family planning program was sluggish because during the pandemic there were no mobile family planning services that involved a lot of mass media and services at health facilities were limited, services were provided by giving pills or condoms to couples of childbearing age who requires repeated family planning, but this method has a very high potential for discontinuation. Suggestions to the Lampung Province BKKBN are to encourage managers of intensive family planning programs to provide mobile family planning services and utilize digital promotional media to inform family planning services.